Analysis of Islamic estate distribution preferences: analytical hierarchy process approach - Mohd Khairy Kamarudin; Mohd Asrul Hery Ibrahim; Nor Azilawati Ahmad; Azwan Abdullah; Siti Fariha Muhamad (Medwell Journals, 2016)
Estate distribution is important to the economic development among Muslims. It must be distributed properly to avoid estate being frozen and become uneconomic to the society. For Muslims deceased’s estate, there are three methods of distribution which are faraid, muafakat and takharruj. It is the aim of this study to identify the preferred distribution that the heirs will choose in the event of death. The Analytical Hierarchy Process (AHP) is utilised to show how the heirs rank these methods of distribution based on their preference. The questionnaire is employed to gather the respondents’ information. This study indicates that the heirs prefer to distribute the estate based on faraid share compared to other methods. This study also recommends that the community should be exposed to other methods of distribution which best suited to their needs.